Comparison of Agricultural Insurance Premium Prices Based on Rainfall Index and Based on Corn Commodity Production Prediction Index in Grobogan District - Tiara Rosady; Agung Prabowo; Bambang Herdriya Guswanto; Jumadil Saputra (Research Collaboration Community (RCC), 2024)
In running an agricultural business, there is a big risk because farmers' productivity is very dependent on nature, and to reduce the risk of crop failure, the government provides a program to minimize losses from crop failure, namely agricultural insurance, through Law Number 19 of 2013 . This article aims to compare agricultural insurance premium prices based on the rainfall index and the production prediction index for corn commodities in Grobogan Regency. The results of this article are based on the reference used of 3% of compensation, namely IDR 344,872.5, and the results that are close to the reference are the price of insurance premiums based on the 5th simple average method corn production prediction index of IDR 356,433.58 . However, the premium price used as a reference previously was the gross premium price from AUTP, so the insurance premium price for Corn Farmers (AUTJ) was obtained, namely IDR 310,385.25. As a result, we obtained premium price results that were closest to the reference from AUTJ, namely at the 4th percentile, when the agricultural insurance premium price based on the rainfall index was IDR 330,155.76 per planting season.